Penanaman Mangrove Tersistem sebagai Solusi Penambahan Luas Tutupan Lahan Hutan Mangrove Baros di Pesisir Pantai Selatan Kabupaten Bantul - Irawan Waluyo Jati; Rudhi Pribadi (Universitas Sebelas Maret, 2017)
The position of Bantul Regency is directly opposite to Ocean Indonesia which has big wave. This conditioncauses coastal communities, especially in Baros sub-village, Tirtohargo Village with NGO Relung to initiatemangrove planting to avoid the danger of flood, abrasion, tsunami and sea breeze that can harm farmers.Mangrove is an important natural resource in the coastal environment, and has three main functions namelyphysical function, biological, and economical. Besides having three main functions, mangrove forest is veryvulnerable to damage. Various difficulties experienced by the people of Baros sub-village in an effort toincrease the area of mangrove forest cover. Appropriate methods are needed to overcome problems by plantingmangrove system. The approach of this study is the literature review from various studies before to provideproper input of mangrove planting in an effort to increase mangrove area in Baros sub-village, Tirtohargovillage, Bantul regency, Yogyakarta.